2020
DOI: 10.1186/s12933-020-01037-0
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying and dose-dependent effect of long-term statin use on risk of type 2 diabetes: a retrospective cohort study

Abstract: Background: We evaluated the effect of statin use on new-onset type 2 diabetes among individuals without atherosclerotic cardiovascular disease (ASCVD) using nationally representative South Korean claims data (2002-2013, N = 1,016,820). Methods: A total of 13,698 patients (statin users 5273, non-statin users 5273) aged 40-74 years, newly diagnosed with dyslipidemia but without any history of diabetes or ASCVD, were selected in 2005. We followed up the final sample until 2013 and evaluated the cumulative incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
3
15
0
1
Order By: Relevance
“…Third, we could not differentiate statins and fibrates from lipid-lowering drugs from the information in CHARLS. The impact of statins treatment on the association between TyG index and diabetes was not fully addressed, considering that statins treatment might increase the risk of developing diabetes (35). Fourth, the follow-up time was relatively short.…”
Section: Limitationsmentioning
confidence: 99%
“…Third, we could not differentiate statins and fibrates from lipid-lowering drugs from the information in CHARLS. The impact of statins treatment on the association between TyG index and diabetes was not fully addressed, considering that statins treatment might increase the risk of developing diabetes (35). Fourth, the follow-up time was relatively short.…”
Section: Limitationsmentioning
confidence: 99%
“…However, in the time since treatment initiation secondary analysis, the result showed that both short-term and long-term PPI usage have elevated CRC risk (HR 1.19, 95% CI 1.03 to 1.34), thereby conflicting with their conclusion. As a result, we suggest that the authors do a secondary analysis of time varying dose dependent model to further clarify the result and strengthen their conclusion 4…”
mentioning
confidence: 57%
“…Some studies have shown that pitavastatin did not adversely affect HbA1c level [ 13 , 38 ]. Recent retrospective study using the Korean insurance claims database reported that the risk of NODM was the largest for atorvastatin followed by rosuvastatin among individual statins when compared to non-statin users, but pitavastatin was not associated with increasing risk of NODM [ 39 ]. However, only 27 patients prescribed with pitavastatin were enrolled in that study.…”
Section: Discussionmentioning
confidence: 99%